What influences decisions about ongoing stroke rehabilitation for patients with pre-existing dementia or cognitive impairment: a qualitative study?. (August 2018) - Longley, Verity; Peters, Sarah; Swarbrick, Caroline; Bowen, Audrey
Objective: To identify factors influencing clinicians decision-making about ongoing stroke rehabilitation for people with pre-existing dementia/cognitive impairment and the impact on clinical practice. Design: Qualitative semi-structured interviews with stroke specialist healthcare professionals analysed using thematic analysis. Setting: Acute stroke unit, inpatient stroke rehabilitation units, and community stroke services. Participants: Twenty three professionals from six multidisciplinary stroke teams involved in decision-making about stroke patients' rehabilitation potential and clinical pathways. Results: Factors influencing decision-making about ongoing rehabilitation were (1) gaining understanding of the individual patient, (2) clinician's knowledge of dementia/cognitive impairment, (3) predicting rehabilitation potential, (4) organizational constraints, and (5) clinician's perceptions of their role within the team. Decision-making led to two outcomes, either accommodating the pre-existing dementia/cognitive impairment within delivery of rehabilitation or ending rehabilitation for that patient to allocate limited resources where they were perceived more likely to be effective. Participants felt that patients with pre-existing dementia/cognitive impairment had difficulty demonstrating the required rehabilitation potential within the short timescales available in the current model of service delivery. Participants identified a need for training to improve their knowledge and confidence for decision-making and delivery of rehabilitation for this growing population. Conclusion: Clinicians' decision-making about ongoing rehabilitation for patients with prestroke dementia/cognitive impairments is influenced by gaps in their knowledge and by service constraints. Increased training and more flexible, patient-centred services would enable clinicians to better accommodate these patients in rehabilitation.